PENGGUNAAN BAHASA PADA PENULISAN MEDIA LUAR RUANG DI KOTA KETAPANG - Nurkumala, Ercita Intan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The background of this study is because the outdoor media is a means to disseminate information to the general public which is located in an open space, such as on a side road and on premises where the community conduct activities. The thing to note is composed of the physical aspects, language aspects, and legal aspects,source from the Center for Development of the Agency for Language Development and Founding. The research method is descriptive method and applies in this study is a qualitative research. The data of this study are the outdoor media in District of Delta Pawan, Ketapang (agencies and private nameplate, business trade center nameplate and place, outdoor advertisings, residential and lodging nameplate, as well as traffic and events signage). The technique used in this study is the observation technique. Based on the results of data analysis and calculation that the use of language on the writing of outdoor media in Ketapang City from the three results are re-summed (the end result of the sum of physical, language, and legal aspects) obtains a 244.5 result. The result defines Ketapang City into the controlled III territory criteria. Keywords: the use of language, outdoor media, Ketapang City